A litispendência no regime especial da coisa julgada - Prado, Pedro Pierobon Costa do (2021)
The Civil Procedural Code of 2015 broke with the previous system to extend the objective limits of the res iudicata to the resolution of incidental issues incidentally ruled in the proceedings. The resolution of the conditional legal relationship can now be resolved in the ruling with res iudicata effect, and the filing of a new lawsuit will not be mandatory if the legal requirements are met. Considering that the incidental issue has potential autonomy and that the objective limits of the material res iudicata may cover the resolution of the question issue, it is necessary to recognize that, from a certain moment prior to the ruling, there will be lis pendens if another autonomous lawsuit with the same claim is filed by either party. This paper aims at analyzing what point in time the incidental issue can no longer be conveyed in another lawsuit, due to lis pendens